2021
DOI: 10.1136/bmjresp-2021-000969
|View full text |Cite
|
Sign up to set email alerts
|

Patients with idiopathic pulmonary fibrosis have poor clinical outcomes with COVID-19 disease: a propensity matched multicentre research network analysis

Abstract: IntroductionOutcomes of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in patients with pre-existing idiopathic pulmonary fibrosis (IPF) remain understudied, and it is unknown if IPF is an independent predictor of worse disease course. Herein, we report the clinical outcomes in a large cohort of 251 patients with COVID-19 in the setting of known IPF. Outcomes were compared with a propensity matched cohort of patients with COVID-19 without IPF.MethodsAnalysis of a federated multicentre r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 9 publications
2
23
1
Order By: Relevance
“…Moreover, it was reported that the major risk factors for severe COVID-19 are shared with PF (George et al, 2020). Comparable to what was said in a previous research, COVID-19 patients with pre-existing PF have been thought to have worse outcomes (Naqvi et al, 2021), which also proved by an international multicenter study (Drake et al, 2020). Most recently, a study reported that chronic COVID-19 patients who received anti-fibrotic therapy obtained a better response in pulmonary function (Kerget et al, 2022).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Moreover, it was reported that the major risk factors for severe COVID-19 are shared with PF (George et al, 2020). Comparable to what was said in a previous research, COVID-19 patients with pre-existing PF have been thought to have worse outcomes (Naqvi et al, 2021), which also proved by an international multicenter study (Drake et al, 2020). Most recently, a study reported that chronic COVID-19 patients who received anti-fibrotic therapy obtained a better response in pulmonary function (Kerget et al, 2022).…”
Section: Discussionmentioning
confidence: 87%
“…PF is thought to be one of the most serious complications in patients recovered from Previous studies suggested that most post-discharge COVID-19 patients have PF sequelae (Sun et al, 2020;Li et al, 2021). COVID-19 patients with pre-existing idiopathic pulmonary fibrosis (IPF) have been thought to have worse outcomes (Naqvi et al, 2021). IPF as a type of PF, is demonstrated to be associated with poor prognosis in non-COVID-19 patients (Lederer and Martinez, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Of note, patients with pre‐existing idiopathic pulmonary fibrosis (IPF) are at high risk for COVID‐19‐related pathology and clinical outcomes. 31 , 32 Additionally, as the gene signatures from COVID‐19 lungs resemble patients who have IPF, antifibrotic therapy may improve outcomes for COVID‐19 patients with an increased risk of development of fibrosis. 27 …”
Section: Clinical Features Of Acute Covid‐19 Immunopathologymentioning
confidence: 99%
“…While there have been conflicting reports on the risk of SARS-CoV-2 infection in patients with chronic pulmonary diseases, especially in asthma patients, 34 35 their increased risk of severe outcomes after infection is well established. [1][2][3][4] Several industrialised countries have introduced additional third and fourth doses to their COVID-19 vaccination schedules in light of the waning immunity after vaccination, which is highly relevant for patients with chronic pulmonary diseases. 35 The identified risk factors for being a low responder have not been extensively characterised for other groups than severely immunocompromised patients.…”
Section: Risk Factors Associated With a Lower Response To Vaccination...mentioning
confidence: 99%
“…Patients with chronic pulmonary diseases, including chronic obstructive pulmonary disease (COPD), interstitial lung disease (ILD), severe asthma and bronchiectasis, are at increased risk of severe and critical COVID-19. [1][2][3][4] In addition, several retrospective cohort studies and case…”
Section: Introductionmentioning
confidence: 99%